(untitled) (ModaPalavra e-periódico, 2010)
This article notes how the trends are influenced by historical, socio-political and economic aspect performing a comparison between these two periods, the crisis of 1929 combined the two Great World Wars influencing the behavior of fashion in Brazil in the decades of 30 to 50 and the current crisis with the political and social events of the beginning of the XXI century influenced the trends.